2015
DOI: 10.1152/jn.00161.2014
|View full text |Cite
|
Sign up to set email alerts
|

Whole-hand water flow stimulation increases motor cortical excitability: a study of transcranial magnetic stimulation and movement-related cortical potentials

Abstract: Maruyama A. Whole-hand water flow stimulation increases motor cortical excitability: a study of transcranial magnetic stimulation and movement-related cortical potentials. J Neurophysiol 113: 822-833, 2015. First published November 5, 2014 doi:10.1152/jn.00161.2014.-Previous studies examining the influence of afferent stimulation on corticospinal excitability have demonstrated that the intensity of afferent stimulation and the nature of the afferents targeted (cutaneous/proprioceptive) determine the effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 66 publications
1
33
0
Order By: Relevance
“…The increase in negativity could be due to an increase in cortical excitability, which has been shown after hand motor skill training where improvements in performance were observed (Pascual-Leone et al, 1995 ). This hypothesis is supported by previous studies that have shown that increases in MRCP amplitude reflect increased cortical excitability (Birbaumer et al, 1990 ; Sato et al, 2015 ). It should be noted, however, that it also has been shown that the MRCP amplitude is inversely correlated with the amplitude of the TMS-elicited motor evoked potential (Lu et al, 2009 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in negativity could be due to an increase in cortical excitability, which has been shown after hand motor skill training where improvements in performance were observed (Pascual-Leone et al, 1995 ). This hypothesis is supported by previous studies that have shown that increases in MRCP amplitude reflect increased cortical excitability (Birbaumer et al, 1990 ; Sato et al, 2015 ). It should be noted, however, that it also has been shown that the MRCP amplitude is inversely correlated with the amplitude of the TMS-elicited motor evoked potential (Lu et al, 2009 ).…”
Section: Discussionsupporting
confidence: 81%
“…A number of studies have reported the effect of induction of plasticity, motor training or skill acquisition on the amplitude of the MRCP segments with conflicting results. Increased amplitudes have both been associated with increased and decreased cortical excitability (Birbaumer et al, 1990 ; Rossi et al, 2000 ; Holler et al, 2006 ; Lu et al, 2009 , 2011 ; de Tommaso et al, 2012 ; Thacker et al, 2014 ; Sato et al, 2015 ), which is also associated with motor skill acquisition (Pascual-Leone et al, 1995 ). In studies investigating motor skill training specifically, the MRCP amplitude has been reported to increase and decrease as well (Taylor, 1978 ; Lang et al, 1983 , 1986 ; Niemann et al, 1991 ; Staines et al, 2002 ; Chiang et al, 2004 ; Smith and Staines, 2006 , 2010 , 2012 ; Wright et al, 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…A great potential for further research of MRPs in PD and also in healthy controls lies in combining different methodologies -EEG and imaging (Nguyen et al , 2014, Plichta et al , 2013, transcranial magnetic stimulation (TMS) (de Tommaso et al , 2012, Sato et al , 2015, or MEG -since every technique has strengths and drawbacks. Furthermore, most of the studies completed to date have used a limited number of electrodes restricted to the central and frontocentral motor regions of the scalp to record MRPs.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 43 , 54 Increase in M1 excitability was also reported in response to large-area non-noxious somatosensory stimuli. This was demonstrated by reduced motor activity threshold, increased amplitude of motor-evoked potentials, and increased intracortical facilitation in response to whole-hand or whole-body water flow stimulation 60 , 61 and in response to whole-hand mesh-flow electrical stimulation. 23 , 24 Thus, the theoretical increase in M1 excitability in large-body compression can be attributed to CIA in our study.…”
Section: Discussionmentioning
confidence: 99%